Analysis of Students' Creativity In Solving Numeracy Literacy Problems on Higher Order Thinking Skills (HOTS) Material On Lines And Angles - Yana, Siti Ida; Panglipur, Indah Rahayu; Anas, Aswar (Department of Mathematics Education, Faculty of Teacher Training and Education, Wisnuwardhana University of Malang, 2024)
The aim of this research is to determine students' creativity in solving numeracy literacy problems on Higher Order Thinking Skills (HOTS) questions on lines and angles. The type of research used is descriptive research. The approach used in this research is a qualitative approach because the research was carried out on systems thinking, namely in the form of an analysis of creativity in solving student problems on Higher Order Thinking Skill (HOTS) questions which will then be processed in depth according to facts obtained in the field or research location. Researchers focus on creativity, ability to solve problems on Higher Order Thinking Skill (HOTS) questions in accordance with student creativity. This research uses various data collection methods, including tests, interviews, and documentation. These three methods are used to collect data and information that helps solve research difficulties by supporting and complementing each other. Students with high mathematical abilities can fulfill all indicators of problem-solving creativity, students with moderate mathematical abilities have one indicator of problem-solving creativity that is not met, students with low abilities cannot fulfill several indicators of problem-solving creativity. So it can be concluded that mathematical abilities can influence students' creativity in solving problems